Fictive locomotion in the fourth thoracic ganglion of the crayfish, Procambarus clarkii - Chrachri, A (J Neurosci, 1990)
Bath application of muscarinic agonists induced rhythmic motor activity in an in vitro preparation of the thoracic nervous system of the crayfish, Procambarus clarkii. In 70% of the cases, the rhythm was organized into 1 of the 2 normal patterns: “backward” walking or “forward” walking. In the rest (30%), the ganglion produced either a series of bursts of impulses or no rhythm at all, just an increase in the tonic activity. When it was isolated from all ascending and descending afferents, the fourth thoracic ganglion was still able to generate rhythmic motor output during bath application of muscarinic agonists. In certain motor neurons, muscarinic agonists induced plateau potentials. Under these conditions, some of these motor neurons were able to change the period of the motor pattern, which might suggest that these motor neurons were part of the central pattern generator (CPG) for locomotion. In the presence of 5 x 10(-6)M TTX, the membrane potential of these motor neurons continued to oscillate with organized rhythmic membrane potential oscillations into 1 of the 2 patterns. Under these conditions, current injection into certain motor neurons demonstrated that they continued to affect the CPG. Two classes of walking leg interneurons have been found. First, there are those with a sustained membrane potential: injection of a steady depolarizing current into some of these interneurons induced rhythmic activity in all thoracic motor nerves, even in the absence of any pharmacological activation. Second, there are those with an oscillating membrane potential: these seemed to enable silent motor neurons to be involved in an ongoing rhythm.